Pola Komunikasi Keagamaan Dalam Keluarga Osing di Desa Kemiri, Kecamatan Singojuruh, Kabupaten Banyuwangi - Sahara Megawati; M Hafidzulloh (Balai Bahasa Provinsi Riau, 2022)
This paper will explore an overview of the communication patterns between parents and children in transmitting religious ethics. This research activity took place in the Osing family in Kemiri Village, Singojuruh District, Banyuwangi Regency. The methods used are introspection, participatory observation, in-depth interviews, and documentation. The results of the research conducted indicate that the communicative interaction between parents and children in the process of transmitting religious ethical values ​​to the Osing family in Kemiri Village is non-mechanical so that it does not have rules that are systematically structured and are directive, effective, commissive, coercive, and dialogical. expressive. The cultural themes found indicate that giving advice from parents to their children contains elements of openness, honesty, and independence so that communication takes place effectively and creates mutual acceptance. Keywords: Communicative interaction, Family, Religious ethics